Os sentidos de violência para adolescentes privados de liberdade: uma experiência no Centro Socioeducativo do Baixo Amazonas – CSEBA - DUTRA, Josefa Antonia de Sousa (Universidade Federal do Oeste do Pará, 2023)
The present dissertation has as its theme “The meanings of violence for adolescents deprived of liberty: an experience in the Socio-Educational Center of Baixo Amazonas” and aims to identify the meanings of violence from the narratives of adolescents in conflict with the law in compliance with the socio-educational measure of hospitalization. The post-structuralist cultural theory (HAAL, 1992), the expansion of the understanding of violence (CHAUÍ, 2003), adolescence (BOCK, 2002), among other authors, were used to discuss and analyze the roots of violence in capitalist society, conceiving identity as a social production and the principles of the National System of Socio-Educational Assistance as a national policy for socio-educational measures were discussed. This is a qualitative research, based on the method of dialectical materialism, with nineteen teenagers from the Socio-Educational Center of Baixo Amazonas, in Santarém/Pará, as subjects. The instruments used consisted of observation, document analysis, visits to the Socio-Educational Center, socio-demographic questionnaire, semistructured interviews and peacemaking circles - Restorative Justice tool used in conflict resolution and criminal justice as an advance in which advocates the Child and Adolescent Statute. Field, bibliographic and documentary research was carried out. Nineteen interviews were carried out with adolescents deprived of liberty, document analysis, application of the sociodemographic questionnaire of the Google Forms tool and the realization of three circles of dialogues with six adolescents in each one. The treatment of the collected data followed the procedures of critical analysis of the content according to Bardin (2002), as well as the discursive textual technique, according to Moraes (2003). The narratives pointed out the categories: rationalization of the crime; affective abandonment; violence/resignation/punishment; social vulnerability/poverty to understand the practice of infractions. From them, the meanings of violence for the interviewed adolescents were identified, such as: violence is a crime according to the law; violence is not violence; Violence directed at affective relationships; violence as an inducement to crime; Violence as punishment; violence as loss and violence as moral judgment.